NOTES ON SONERILA CELEBICA (MELASTOMATACEAE) - Abdulrokhman Kartonegoro (PTTI, 2011)
Based on analysis of morphological characters, Sonerila celebica and S. froidevilleana are recognized as conspecific. Consequently, S. froidevilleana is sunk as a synonym of S. celebica.